Analisis Pengaruh Bantuan Sosial Bersyarat Program Keluarga Harapan terhadap Partisipasi Pendidikan Anak Usia Sekolah di Indonesia - Vianti, Devi Irma; Fauziah, Fauziah (Jurnal Kebijakan Ekonomi, 2023)
The purpose of this research is to analyze the impact of Conditional Social Assistance of Program Keluarga Harapan (PKH) on School Age Educational Participation in Indonesia. Population in this research were all household (HH) with children aged 7 to 18 years. Data was obtained from the National Socio-Economic Survey in 2018 and 2018 Village Potential. Data refers to the use of Net Enrollment Rate (NER). Data was clustered into the group of ES, ES-JHS, and ES-SHS. Technical analysis used is binary logistic regression. The results indicate that PKH has an effect in increasing the School Age Educational Participation in Indonesia.